USING PUBLIC DIPLOMACY FOR CREATING INTERNATIONAL PEACE AND SECURITY – THE CASE OF POLAND AND SWEDEN - Zajęcki, Rafał; Shuliak, Antonina; Fesyk, Olesya (Torun International Studies, 2020)
In the period of democratisation and mediatisation, public diplomacy became a significant part of foreign policies of many states. Today’s governments notice and appreciated its role in coordinating and implementing strategic activities consisting in shaping such an external environment that supports the foreign policy of a given state by understanding, properly informing and influencing global public opinion. A positive image of the state on the international arena strengthens its credibility and voice in the debate on global issues and policies, which in turn enables it to achieve its goals more effectively. Apart from social and economic spheres, public diplomacy activities may also strive to ensure security and stability in a given part of the world. Thus, the aim of this article is to analyse the phenomenon of public diplomacy and its impact on creating international norms of security. A comparative method used herein is aimed at answering the following question: how does Polish and Swedish public diplomacy activities contribute to creating the world’s peace and security. In the article, the perspective of constructivism referring, among others, to the issue of national identity as a causal factor for states’ activities, was used.